Healthcare Associated Inadvertent Intra-Arterial Injection as a Cause of Acute Limb Ischemia - Fahad Memon, Mohammad Fahad Tariq Barlas, Areeba Saleem, Waryam Panhwar, Najam Uddin Rajper, Khalil U Rehman, Ayesha Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The present study aimed to determine the outcome of healthcare related inadvertent intra-arterial injection as a cause of acute upper limb ischemia in terms of limb function and salvageability. Methods: A retrospective observational study was undertaken at the Department of Vascular and Endovascular Surgery, Shaheed Mohtarma Benazir Bhutto Institute Of Trauma, Karachi between 1st January 2020 to 31st December 2021. All patients who presented with ischemia secondary to inadvertent intra-arterial injection between the ages 18-70 years were included in the study. Files of the patients were reviewed and data was gathered to fill proformas. Follow up of the patients was reviewed for up to four months. Acute limb ischemia, limb salvageability, and limb function was assessed post-treatment. Results: In 14 (46.67%) no amputation occurred, 5 (16.67%) had minor amputation while 11 (36.67%) had major amputation. Seriousness of presenting symptoms was significantly associated with major amputation (p = 0.022). The majority of the patients who presented with pain, discoloration, sensory loss, motor loss, and gangrene had major amputations i.e. 4 (36.4%). memory loss was significantly associated with major amputation [8 (72.7%); p<0.0001]. Gangrene was also significantly associated with major amputation [8 (72.7%); p=0.002]. Conclusion: A number of mechanisms, including direct artery damage, arterial spasm, toxicity from the drug, embolism can result in ischemia following intra-arterial drug injection. In order to avoid such incidents and to make prompt diagnosis, healthcare providers should broaden their awareness of typical local injection practices, phases of injection drug use and the hazards connected with it. Keywords: Acute limb ischemia, gangrene, Injections, Intra-Arterial, Ischemia